On quasi quantum quadratic operators of M_2(C) - Mukhamedov, Farrukh; Abduganiev, Abduaziz (Springer Science+Business Media Singapore 2014, 2014)
In the present paper we study quasi quantum quadratic operators (q.q.o) acting on the algebra of 2 × 2 matrices M2(C). We describe quasi q.q.o. with Haar state, and prove that if a symmetric quasi q.q.o. with Haar state is q-pure, then it cannot be positive.